2017
DOI: 10.1111/febs.14109
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the importance of the malaria parasite helicases

Abstract: Malaria is a human parasitic disease caused by infection from Plasmodium species, particularly Plasmodium falciparum. Each year millions of people are infected with malaria and large numbers of deaths result due to this deadly infection. P. falciparum contains 14 chromosomes, nearly 5400 genes and a multistage life cycle in humans and mosquitoes. The control of malaria is still a challenge as the parasite is continuously developing resistance to available antimalarial drugs and the mosquito vector is developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 95 publications
(204 reference statements)
0
10
0
Order By: Relevance
“…Genome analyses have revealed that P. falciparum contains several parasite-specific helicases in addition to homolog of human helicases. Development of inhibitors that specifically target the helicases unique to P. falciparum would help to cure malaria (Tuteja, 2017 ).…”
Section: Dna Helicases An Emerging Target For Cancer Therapymentioning
confidence: 99%
“…Genome analyses have revealed that P. falciparum contains several parasite-specific helicases in addition to homolog of human helicases. Development of inhibitors that specifically target the helicases unique to P. falciparum would help to cure malaria (Tuteja, 2017 ).…”
Section: Dna Helicases An Emerging Target For Cancer Therapymentioning
confidence: 99%
“…Due to this increasing resistance towards modern day front line antimalarials there is an urgent need to develop new range of antimalarial drugs and to identify novel chemotherapeutic targets 9 . Helicases are ubiquitous and present in every organism such as bacteria, virus, yeast, plants, human, and the malaria parasite Plasmodium 10 , 11 . Significant part of our genome encodes helicases, which proves the importance of these molecules 12 .…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue on Malaria brings together cutting‐edge research and timely review articles to present a current overview of this expansive field. In this issue, five experts review key topics in malaria research, including the progress toward vaccine development , the problem of drug resistance , the artemisinin‐based combination therapy , the importance of helicases in malaria parasite biology , and the use of malarial proteases as viable drug targets . Four original studies from highly active malaria research groups present groundbreaking work on the P. falciparum ‐specific iron‐sulfur [Fe‐S] assembly pathway , characterization of an immunogenic P. falciparum surface protein for vaccine development , identification of amino acid substitutions that underlie metabolic adaptation in a P. falciparum mono‐acid transporter , and identification of origins of replication in the P. falciparum genome .…”
mentioning
confidence: 99%
“…The review also discusses the efficiency of different ACTs compared to the usage of the partner drugs alone . The fourth review of the series highlights the helicases present in the P. falciparum genome . Helicases are motor proteins that play vital roles in nucleic acid unwinding by harnessing the energy derived from ATP hydrolysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation